2015
DOI: 10.1021/acs.organomet.5b00194
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Carbon–Sulfur Bond Activation by a Reactive (dippe)Pd Fragment

Abstract: Supporting Information Table of Contents ________________________________________________________________________________________Experimental details for the structure determination of 9. S-72Experimental details for the structure determination of 10. S-93Experimental details for the structure determination of 14. S-106Experimental details for the structure determination of 14 and 15. S-126Experimental details for the structure determination of (dippe)Pd(Cl) 2 . S-143

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Recently, Jones reported that dippe-ligated palladium complex can cleave the C-S bond of diphenyl sulfide even at room temperature [12,21]. They prepared an equivalent of 14-electron Pd(dippe) by reducing PdCl2(dippe) with NaHBEt3.…”
Section: Scheme 8 Oxidative Addition Of Vinyl Sulfide To Platinum Commentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Jones reported that dippe-ligated palladium complex can cleave the C-S bond of diphenyl sulfide even at room temperature [12,21]. They prepared an equivalent of 14-electron Pd(dippe) by reducing PdCl2(dippe) with NaHBEt3.…”
Section: Scheme 8 Oxidative Addition Of Vinyl Sulfide To Platinum Commentioning
confidence: 99%
“…disproportionation into nickelathiacycle 12, dinuclear Ni(I) μ-sulfide complex 13, and dibenzothiophene in a ratio of 1:1:2. Later, platinum [11] and palladium [12] analogues of 11 having the strongly electron-donating dippe ligand were also isolated.…”
mentioning
confidence: 99%
“…We have recently reported rapid C–S activation of thiophenes by a mixture of [Pd­(dippe)­(μ-H)] 2 ( 1a ) and dinuclear Pd(0), [(μ-dippe)­Pd] 2 ( 1b ) (dippe = 1,2-bis­(diisopropylphosphino)­ethane), to generate palladium­(II) C–S activated products . The mixture of complexes 1a and 1b furnishes the highly reactive 14-electron (dippe)Pd fragment, which is responsible for the activation of the carbon–sulfur bonds in thiophenes and thioethers.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has also investigated the activation of thiophene using precursors for the reactive [12,13], Pd [14,15], and Pt [14]. The [Pt(dippe)] fragment showed unique reactivity in that it was observed to insert into the hindered C-S bond of 4,6-dimethyldibenzothiophene (eq 1) [16].…”
Section: Methodsmentioning
confidence: 99%